2022
DOI: 10.1128/spectrum.00436-22
|View full text |Cite
|
Sign up to set email alerts
|

A Cytoplasmic NAD(P)H-Dependent Polysulfide Reductase with Thiosulfate Reductase Activity from the Hyperthermophilic Bacterium Thermotoga maritima

Abstract: The reduction of S 0 and thiosulfate is essential in the sulfur cycle of geothermal environments, in which thermophiles play an important role. Despite previous research on some sulfur reductases of thermophilic archaea, the mechanism of sulfur reduction in thermophilic bacteria is still not clearly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is not improbable that the members of the Fusibacter genus can perform disproportionation of thiosulfate and sulfite, as it was shown for Desulfovibrio sulfodismutans [ 35 ], Desulfocapsa thiozymogenes [ 36 ], and bacteria belonging to Nitrospirota [ 37 ]. Additionally, the hyperthermophilic obligate anaerobic bacterium Thermotoga maritima is able to utilize diverse carbohydrates, but the cellular mechanism of sulfate reduction for this species has not been fully understood yet; this strain also possesses NAD(P)H-dependent polysulfide reductase with S 0 and thiosulfate reductase activities [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not improbable that the members of the Fusibacter genus can perform disproportionation of thiosulfate and sulfite, as it was shown for Desulfovibrio sulfodismutans [ 35 ], Desulfocapsa thiozymogenes [ 36 ], and bacteria belonging to Nitrospirota [ 37 ]. Additionally, the hyperthermophilic obligate anaerobic bacterium Thermotoga maritima is able to utilize diverse carbohydrates, but the cellular mechanism of sulfate reduction for this species has not been fully understood yet; this strain also possesses NAD(P)H-dependent polysulfide reductase with S 0 and thiosulfate reductase activities [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TMHMM protein transmembrane analysis showed that YedE1 and YedE2 each contained four transmembrane helixes, and EcYedE3 had nine transmembrane helixes. YedE3 mediates thiosulfate uptake in E. coli, Spirochaeta thermophila, and Metallosphaera cuprina [36][37][38]. Thus, YedE1 and YdeE2 were likely forming a transporter (YedE1E2).…”
Section: Sequence Analysis Indicates Yede and Yed1e2 Are Membrane Pro...mentioning
confidence: 99%